East Asian patients who received immunotherapy‐based therapy associated with improved survival benefit in advanced non‐small cell lung cancer: An updated meta‐analysis - Yueyuan Yao; Butuo Li; Yiyue Xu; Linlin Yang; Bing Zou; Linlin Wang (Cancer Medicine, 2024)
Abstract Background Immune checkpoint inhibitors (ICIs) combined with chemotherapy have been recommended as the standard treatment for advanced NSCLC patients without driver‐gene mutations. However, there are different genetic characteristics and biological traits of tumors between non‐East Asian (nEA) and East Asian (EA) patients with NSCLC, which may contribute to differences in the efficacy of ICIs in different ethnic populations. Previous findings regarding differences in the efficacy of ICIs among ethnic groups have been inconsistent. Therefore, we performed a meta‐analysis by collecting published data to investigate the clinical outcomes of ICIs for EA NSCLC patients compared to nEA patients. Methods Overall survival (OS) and progression‐free survival (PFS) were used to access the difference in survival outcomes between the two populations. Subgroup analyses were performed based on the line of ICIs, the use of ICIs alone or in combination, and the type of ICIs. Results A total of 9826 NSCLC patients from 21 randomized controlled trials (RCTs) with 4064 EAs were included, which involved PD‐1, PD‐L1, and CTLA‐4 inhibitors. EA NSCLC patients who received ICIs‐based therapy were associated with significantly improved survival benefits in OS (p = 0.02) compared with nEA patients. Subgroup analysis indicated that EA patients receiving first‐line ICIs showed significantly superior OS compared with nEA patients (p = 0.007). Chemo‐ICIs treatment showed significant advantages in terms of OS (p = 0.002) and PFS (p = 0.02) among EA patients compared to nEA patients. In addition, PD‐1 inhibitors were associated with improved OS among both EA patients and nEA patients compared with PD‐L1 inhibitors. Conclusion EA NSCLC patients who received ICIs‐based therapy were associated with significantly improved survival benefits compared with nEA NSCLC patients. Earlier intervention with ICIs and combination treatment was more recommended for EA NSCLC patients. Moreover, PD‐1 inhibitors are associated with prolonged survival among both EA and nEA patients.